Penerapan Aloe Vera Gel untuk Penyembuhan Luka Diabetik di Wilayah Boyolali - Sinta Azzahra Lucia Agustin; Ida Nur Imamah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Diabetic ulcers is a complication of diabetes mellitus resulting from autonomic neuropathy and/or vascular disorders of the limbs. One of the diabetic ulcer treatment techniques is using aloe vera gel contains anti-bacterial, anti-inflammatory and can repair tissue damage of diabetic ulcers.. To determine changes after applying aloe vera gel to diabetic ulcer wound healing. This research uses descriptive case studies by observing nursing care for diabetic ulcer patients using aloe vera gel at the Boyolali with an application 3x and application is carried out every 2 days using the Bates-Jensen Wound Assessment Tool. Results: The results of the assessment score before application in respondent 1 score 24 points with categories wound regeneration and respondent 2 score 30 points with categories wound regeneration. After application with aloe vera gel the score on respondent 1 was 14 points with categories wound regeneration while on respondent 2 was 11 points with categories Tissue Health. The application of aloe vera gel can be used as an effective nonpharmacological method for diabetic ulcer wound.